2023
DOI: 10.2196/preprints.46918
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Influencing Co-Morbid Suicidal Ideation among Newly diagnosed HIV/AIDS Patients in Shenzhen: A Structural Equation Model (Preprint)

Abstract: BACKGROUND HIV co-morbid suicidal ideation is an important public health problem. And the prime time for suicide ideation intervention among newly diagnosed HIV/AIDS patients in the early stage of HIV/AIDS diagnosed. OBJECTIVE This study aims to apply structural equation modeling to investigate suicidal ideation among newly diagnosed HIV-infected patients to provide a basis for subsequent inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…Number of participants ranged from 244 in a Chinese cohort [49] to 34528 in an African cohort [43], and a total of 121142 participants across 15 countries participated in the 29 included studies. More than half of the studies (n = 16) [37,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] were conducted in Asia, followed by Africa (n = 9), Europe (n = 3) [32,35,40] and North America (n = 1) [39]. The target population included ART-initiated patients and HIV-positive patients including patients who did not start treatment.…”
Section: Study Results and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Number of participants ranged from 244 in a Chinese cohort [49] to 34528 in an African cohort [43], and a total of 121142 participants across 15 countries participated in the 29 included studies. More than half of the studies (n = 16) [37,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] were conducted in Asia, followed by Africa (n = 9), Europe (n = 3) [32,35,40] and North America (n = 1) [39]. The target population included ART-initiated patients and HIV-positive patients including patients who did not start treatment.…”
Section: Study Results and Characteristicsmentioning
confidence: 99%
“…Seven studies reported the mean time to initiate ART after HIV confirmation, ranging from five to 40 days [32,35,36,46,47,49,52]. In addition, 18 studies used a cohort [32-37, 39, 41-45, 48-52, 54] design, 10 studies used a cross-sectional design [40,46,47,53,[55][56][57][58][59][60], and one study [38] used quasi-experimental study. We evaluated the quality of 28 of 29 studies.…”
Section: Study Results and Characteristicsmentioning
confidence: 99%